Reducing Public Anxiety in Students Through Behavioral Counseling with Systematic Decentization Techniques - Ni Kadek Oki Yuniantari; I Ketut Gading; Kadek Ari Dwiarwati (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The large number of students who experience anxiety about communicating in public is generally caused by a lack of self-confidence when communicating in public, so to overcome this problem, guidance is needed to improve students' abilities. This research aims to determine whether behavioral counseling using systematic desensitization techniques effectively reduces students' communication anxiety. This research is classified as quantitative using a quasi-experimental approach with a Non-equivalent Control Group design. The population in this study was 199 junior high school students. Sampling was carried out by scanning to obtain subjects, so 32 students were obtained as respondents, then divided into 2, where the results obtained were 16 students who had high category anxiety in communicating in public. Data collection on public communication anxiety was collected using this research data collection method using primary data, a questionnaire technique with a Likert scale. Instrument validity testing was carried out by consulting with experts (expert judgment), while instrument reliability testing used the Alpha Cronbach formula. The results of the research analysis show that the calculated F' score (F'h) is 26.923 with a degree of freedom (df) of 31 and a significance score (Sig) of 0.00. This score is compared with the F table score (F't), which has the same df. As a result, the calculated F' score (26.923) is greater than the table F' score (2.659). So, based on the results of this research, it can be concluded that behavioral counseling using systematic desensitization techniques has proven effective in reducing junior high school students' anxiety about communicating in public.